«The new land»: resettlement areas and their development - Podvintsev, O.B. (Perm Federal Research Centre Journal, 2018)
In the framework of the study into empires and post-imperial political systems, a special attention is paid to resettled territories, the so-called «New lands». In this paper, the plan of the book and some materials are presented. They are dedicated to a variety of problems related to the development of “New lands”, as well as their destinies during post imperial times.